2019
DOI: 10.3390/membranes9060073
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Feed Solution Temperature on the Power Output Performance of a Pilot-Scale Reverse Electrodialysis (RED) System with Different Intermediate Distance

Abstract: Membrane-based reverse electrodialysis (RED) can convert the salinity gradient energy between two solutions into electric power without any environmental impact. Regarding the practical application of the RED process using natural seawater and river water, the RED performance depends on the climate (temperature). In this study, we have evaluated the effect of the feed solution temperature on the resulting RED performance using two types of pilot-scale RED stacks consisting of 200 cell pairs having a total effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…To keep the CEMs and AEMs separated and allow the feed solutions to circulate in the RED stack without mixing one to another, spacers are used. The spacers arranged between the IEMs are designed to preserve their intermediate distance 116 and enhance the mass transfer by facilitating turbulence in the system 97 . They are usually made of woven materials (non‐conductive) and using such materials in an RED stack causes a massive drop in energy production efficiency.…”
Section: Reverse Electrodialysismentioning
confidence: 99%
See 2 more Smart Citations
“…To keep the CEMs and AEMs separated and allow the feed solutions to circulate in the RED stack without mixing one to another, spacers are used. The spacers arranged between the IEMs are designed to preserve their intermediate distance 116 and enhance the mass transfer by facilitating turbulence in the system 97 . They are usually made of woven materials (non‐conductive) and using such materials in an RED stack causes a massive drop in energy production efficiency.…”
Section: Reverse Electrodialysismentioning
confidence: 99%
“…In a cause‐effect base, when temperature increases, the solution conductivity increases as well, and ionic mobilities are facilitated, ohmic losses are reduced resulting in higher power output 97 . Stack resistance being well known as a key parameter in an RED unit, it is obvious that temperature may influence the RED performance by influencing the resistance of the feed solution 116 . Guo et al reported that with the rising temperature, the OCV increases and the internal resistance reduces, as a result, higher power density is generated 123 .…”
Section: Reverse Electrodialysismentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration and temperature of RED's inlet streams will determine the net power density of the system; the more concentrated and warmer the feeds, the larger the net power output of the RED plant (green to yellow hues in the map, Figure 3) [29,[67][68][69]. As such, the SWRO plants located in the Middle East (i.e., scenarios 1, 9 and 15), suppling the most concentrated and warmest brine effluent to RED, enhance the net power density (3.6-3.7 W m −2 per cell pair; Figure 3) peaking to~4.0 W m −2 per cell pair in scenario 12.…”
Section: Net Power Density and Net Specific Energy Of The Red Systemmentioning
confidence: 99%
“…or temperature (20 • C)[24,67,69] bring about improved net power densities (3.5 W m −2 per cell pair and 3.4 W m −2 per cell pair, respectively). Conversely, the net power density almost halves (~2.1 W m −2 per cell pair) in scenarios with opposite working conditions (e.g., scenarios 14 and 20;Figure 3), where RED draws energy from the coldest and more diluted SWRO concentrate effluents.Appl.…”
mentioning
confidence: 99%